2017
DOI: 10.3892/or.2017.5592
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a promotes proliferation, migration, and invasion of colorectal cancer by targeting FAM172A and acts as a diagnostic and prognostic biomarker

Abstract: Accumulating evidence shows that mircroRNAs (miRNAs) play a crucial role in the development of colorectal cancer. In our previous study, FAM172A was demonstrated to be a novel tumor suppressor gene in CRC. Therefore, the aim of the present study was to identify whether the miR‑27a could be a diagnostic and prognostic marker and the regulatory relationships between miR‑27a and FAM172A. We demonstrated high levels of miR‑27a expression in tissues of patients with CRC as well as in CRC cell lines. There was a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
9
11
0
Order By: Relevance
“…Furthermore, following the growth in MCS, both cell lines exhibited a subset of 16 differentially expressed miRNAs. The significance of our observations is supported by previous reports indicating that miR-200a-3p [39], miR-141-3p [40], miR-375 [41], miR-194-5p [42], miR-27a-3p [43] and miR-29b-3p [42] could be clinically applied as potential CRC biomarkers. In addition, miR-194 was shown as one of the most deregulated miRNAs in cancerous tissue as well as miRNAs of the miR-200 family, including miR-200b and miR-200c [44].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, following the growth in MCS, both cell lines exhibited a subset of 16 differentially expressed miRNAs. The significance of our observations is supported by previous reports indicating that miR-200a-3p [39], miR-141-3p [40], miR-375 [41], miR-194-5p [42], miR-27a-3p [43] and miR-29b-3p [42] could be clinically applied as potential CRC biomarkers. In addition, miR-194 was shown as one of the most deregulated miRNAs in cancerous tissue as well as miRNAs of the miR-200 family, including miR-200b and miR-200c [44].…”
Section: Discussionsupporting
confidence: 89%
“…Our further studies will focus on this miRNA to throw more light on this difference. miR-27a is one of the least studied miRNAs in the literature (36,37). During our research we found that this miRNA showed very similar behavior both in meso-and hypopharyngeal carcinomas as miR-21.…”
Section: Discussionsupporting
confidence: 59%
“…Data from GSE39833 showed that both circulating exosomal miR-27a and miR-130a were potential diagnostic biomarkers for colorectal cancer, which was validated in our subsequent experiments. Liu and colleagues revealed that miR-27a promotes proliferation, migration, and invasion of colorectal cancer by targeting FAM172A (30). Chen and colleagues demonstrated that miR-130a is upregulated in colorectal cancer and promotes cell growth and motility by directly targeting forkhead box F2 (FOXF2; ref.…”
Section: Discussionmentioning
confidence: 99%